Clinical implication of protostlylid: a point of view from dental anthropology and non-invasive dentistry - Sandra Milena Moreno-Correa; Freddy Moreno-Gómez (Universidad de Antioquia, 2021)
According to the multifactorial pathological model, dental morphology has been associated as one of the etiological factors of caries by favoring the accumulation of food remains and biofilm retention. One of the most frequent of non-metric dental traits of the Colombian population is the P point of the protostylid, which is constituted in a fossa that is expressed in the bucomesial development groove of the lower molars, a region that follows the occlusal surface as one of sites where carious lesions develop more frequently. However, the lack of knowledge of this morphological feature by most dentists makes the morphological system of the protostylid misdiagnosed, which in many cases leads to the overtreatment of this pit with invasive therapies, which could be avoided with a knowledge adequate dental morphology and with a preventive management or non-invasive techniques. Therefore, the aim of this review of the subject is to reconcile the expression of the P point of the protostylid and to make an approximation to the clinical implications of the same and the conservative diagnostic and therapeutic possibilities offered by dentistry to control the accumulation of food rests and retention of dental biofilm.